The riot of the silversmiths at Ephesus (Acts 19:23-40): A synchronic study using rhetorical and semiotic methods of analysis. - Duffy, Maureen E. (University of Ottawa (Canada), 1994)
Abstract Not Available.
Keywords: Religion, Biblical Studies.